Authorizing Experience : Refigurations of the Body Politic in Seventeenth-Century New England Writing - Egan, Jim (Book collections on Project MUSE., 2001)
The emphasis on practical experience over ideology is viewed by many historians as a profoundly American characteristic, one that provides a model for exploring the colonial challenge to European belief systems and the creation of a unique culture. Here Jim Egan offers an unprecedented look at how early modern American writers helped make this notion of experience so powerful that we now take it as a given rather than as the product of hard-fought rhetorical battles waged over ways of imagining one's relationship to a larger social community. In order to show how our modern notion of experienc.